Developing tailored planning models for forensic organisations. Issue 4 (4th July 2017) - Freitag, Carsten; Found, Bryan
Abstract : Forensic laboratories traditionally focus on the development of scientific excellence to gain and maintain expertise and capability for their core purpose with respect to the provision of sound, impartial analysis of potential evidence, while managing increasingly tight budgets and growing demand. One downside to this primary focus is the lower prioritisation afforded to strategic and operational planning, despite its potential to substantially improve service delivery and enhance efficiency. Here, we focus on traditional planning models used by forensic laboratories and their shortfalls, and we examine options for improvement. Contemporary planning methodologies are assessed for their applicability and one improved planning model is developed and its potential benefits are evaluated.